Pendampingan Ibu Hamil Dalam Upaya Deteksi Dini Resiko Tinggi Kehamilan - Lia Dwi Prafitri; Suparni Suparni; Gigih Setianto (Journal of Community Development, 2025)
The Maternal Mortality Rate (MMR) is a crucial indicator to assess public health, reflecting female deaths due to complications of pregnancy, childbirth, and postpartum per 100,000 live births. In Indonesia, MMR is still high, reaching 305 per 100,000 live births, mainly due to the lack of early detection of the high risk of pregnancy. Assisted activities for pregnant women in the Working Area of the Tirto I Health Center, Pekalongan Regency, to improve the detection and management of high-risk of pregnancy. This activity was carried out through a community empowerment program involving 32 pregnant women from Samborejo Village and Pandanarum Village, for eight months. The methods used include socialization, mentoring, and continuous education with the Islamic Religion and Health approach. The results of the activity showed an increase in pregnant women's knowledge about pregnancy risks, increased community participation, and early identification of risky medical conditions such as pre-eclampsia, KEK, anemia, and hypertension. Emotional and psychological support is provided through an Islamic values-based approach, which helps reduce stress and improve the mental health of pregnant women. Collaboration between the service team, village midwives, and health cadres strengthens efforts to detect and handle the high risk of pregnancy. This program successfully increased the knowledge of pregnant women by 13% and sufficient knowledge by 3% about the prenatal care. It reduced the risk of pregnancy complications, which ultimately contributed to the reduction of maternal mortality and infant mortality rates in the Tirto I Health Center Working Area.. Evaluation and follow-up show that the main goal is achieved and recommend future improvements. Efforts are needed to increase collaboration between various parties such as health offices, health centers, universities, and community organizations to create a stronger support network for early detection of high-risk pregnancies.